2015
DOI: 10.1177/0267658315608912
|View full text |Cite
|
Sign up to set email alerts
|

Production and perception of the English /æ/–/ɑ/ contrast in switched-dominance speakers

Abstract: This study investigates how fluent second-language (L2) learners of English produce and perceive the /æ/–/ɑ/ vowel contrast of Southwestern American English. Two learner groups are examined: (1) early, proficient English speakers who were raised by Spanish-speaking families but who became dominant in English during childhood and, as adults, lack communicative abilities in Spanish, and (2) Spanish-speaking late learners of English who continue to be dominant in Spanish. The participants provided data in three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 55 publications
1
19
0
1
Order By: Relevance
“…Participants reported that they used English more than Spanish in their daily lives, and they were found to be significantly more proficient in English than in Spanish according to their d’ scores on the extended lexical decision tasks ( t (31) = 9.89; p < .001). Proficiency scores on the various measures were in line with norms for this population of Spanish-English bilinguals (Casillas & Simonet, 2016; Kohnert, Hernandez, & Bates, 1998). …”
Section: Methodssupporting
confidence: 74%
“…Participants reported that they used English more than Spanish in their daily lives, and they were found to be significantly more proficient in English than in Spanish according to their d’ scores on the extended lexical decision tasks ( t (31) = 9.89; p < .001). Proficiency scores on the various measures were in line with norms for this population of Spanish-English bilinguals (Casillas & Simonet, 2016; Kohnert, Hernandez, & Bates, 1998). …”
Section: Methodssupporting
confidence: 74%
“…Although participants were competent users of both languages, they were significantly more proficient in English than in Spanish according to their d' scores on the extended lexical decision tasks (t(59) = 11.97; p < .001) and their percent correct scores on the MINT (t(59) = 10.71; p < .001). Scores on the various proficiency measures in each language were comparable to norms for this population of Spanish-English bilinguals (Casillas & Simonet, 2016;Kohnert, Hernandez, & Bates, 1998).…”
Section: Participantsmentioning
confidence: 60%
“…However, it is not the first to show the critical importance of the first years of life on an individual’s phonological development. Several studies have examined the speech production abilities of adults who, as children, were exposed to a language without ever acquiring it (Au, Knightly, Jun, & Oh, 2002; Casillas & Simonet, 2016; Knightly et al, 2003; Oh, Jun, Knightly, & Au, 2003). For instance, Knightly et al (2003) showed that adults, who were not able to speak Spanish but who were passively exposed to the language as children, had more native-like Spanish pronunciation than typical late L2 learners.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the childhood overhearing advantage seems to be domain specific: it was robust in phonology, a domain that is easy for children to acquire but difficult for adults to master, but was not detectable in morphosyntax (Au et al, 2002). Casillas and Simonet (2016) recently examined the production and perception of the /æ/-/ɑ/ vowel contrast by a group of proficient English speakers who were raised by Spanish-speaking families but who became dominant in English during childhood and, as adults, lacked communicative abilities in Spanish, together with a group of Spanish-speaking late learners of English who were dominant in Spanish. Both experimental groups differed from native controls in their production and perception of the English-specific vowel contrast.…”
Section: Discussionmentioning
confidence: 99%